The analysis of main factors to support the regional economic recovery using mangrove rehabilitation activity in Jakarta - A'am Azmiyah; Endang Hilmi; Sudarmalik Sudarmalik (MAIYAH, 2022)
The activity of mangrove rehabilitation in Angke Kapuk, North Jakarta is the ecosystem recovery activities to support the sustainability of mangrove resources to provide economic opportunities for coastal community. This study aimed to determine the main factors and the important variables of economic recovery through mangrove rehabilitation activities and the relationship between variables using the MICMAC (matrix of cross impact multiplications applied to a classification) analysis. The results of the study showed that key variables or driving variables (Influence Variables) were policy factors which high influence for the economic recovery. The Relay Variables consistedf mangrove rehabilitation activity which divided into potential of seeding, planting, counseling, and training. The Dependence Variables consisted economic factors such as the income of ecotourism activity, fisherman, angler, traders, the group of mangrove business, forest farmer group, the price and selling potency of mangrove seedling, price and income of mangrove products. And Autonomous Variables consisted business investors and the price of fish selling.